1980
DOI: 10.1083/jcb.87.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Rotation and twist of the central-pair microtubules in the cilia of Paramecium.

Abstract: The orientation and configuration of the central-pair microtubules in cilia were studied by serial thin-section analysis of "instantaneously fixed" paramecia. Cilia were frozen in various positions in metachronal waves by such a fixation . The spatial sequence of these positions across the wave represents the temporal sequence of the positions during the active beat cycle of a cilium . Systematic shifts of central-pair orientation across the wave indicate that the central pair rotates 360°counterclockwise (vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 36 publications
(61 reference statements)
3
79
0
Order By: Relevance
“…Our data do not address the role of central apparatus twist during beating. Most likely, twist allows for regulation of dynein activity along the length of the axoneme as predicted by Omoto and Kung (18).…”
Section: Precision Of Central Apparatus Orientation In High and Low Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data do not address the role of central apparatus twist during beating. Most likely, twist allows for regulation of dynein activity along the length of the axoneme as predicted by Omoto and Kung (18).…”
Section: Precision Of Central Apparatus Orientation In High and Low Cmentioning
confidence: 99%
“…The central apparatus in Chlamydomonas, as well as in other organisms, is reported to twist (9,18,55). In each case, the twist is left-handed, though the pitch of the twist is variable.…”
Section: Precision Of Central Apparatus Orientation In High and Low Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier studies on lipotubuloid movement in O. umbellatum revealed that in a vigorously rotating lipotubuloid microtubules exhibited different widths or diameters on longitudinal (Kwiatkowska 1972) or cross (Kwiatkowska et al 2009) sections, respectively. The use of OsO 4 for direct fixation of microtubules, due to its quick penetration, allowed to maintain their structure identical to that observed in vivo (Omoto and Kung 1980). Differences in size were even visible in the microtubules consisting of the same number of protofilaments (Kwiatkowska et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The geometry of this regulatory mechanism presumably favors an outer cylinder of precisely nine doublet microtubules, with the distance between doublets determined by the reach of dyneins that must span each interdoublet gap. Whether central pair regulation was based on a fixed central pair orientation, as found today in metazoans such as bivalves 48 , sea urchins 49 , and ctenophores 50 and possibly in excavates such as euglenids 51 , or a rotating central pair 52 , as commonly found in green algae such as Chlamydomonas 53 and Micromonas 54 , and chromalveolates such as Paramecium 55 and Synura 56 , remains to be determined. Central pair rotation may allow regulation of bends in different beat planes, and therefore be a more flexible regulatory system for organisms whose survival is most highly dependent on rapid changes in flagellar beat parameters 47,53 .…”
Section: The Origins Of 9+2 Flagellamentioning
confidence: 99%